2011
DOI: 10.1016/j.biopsycho.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Biological mechanisms underlying the relationship between stress and smoking: State of the science and directions for future work

Abstract: Theories of addiction implicate stress as a crucial mechanism underlying initiation, maintenance, and relapse to cigarette smoking. Examinations of the biological stress systems, including functioning of the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS), have provided additional insights into the relationship between stress and smoking. To date, convergent data suggests that chronic cigarette smoking is associated with alterations in HPA and ANS functioning; however, less is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 165 publications
(203 reference statements)
3
72
0
2
Order By: Relevance
“…Additionally, it has been suggested that high cortisol levels may influence reward-related pathways, enhancing the reinforcement proprieties of drugs (Richards et al, 2011;Sinha, 2008). In this context, hypercortisolism would be expected in carriers of the rs5522-Val and rs6198-G alleles (DeRijk, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, it has been suggested that high cortisol levels may influence reward-related pathways, enhancing the reinforcement proprieties of drugs (Richards et al, 2011;Sinha, 2008). In this context, hypercortisolism would be expected in carriers of the rs5522-Val and rs6198-G alleles (DeRijk, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, smoking has been implicated in the AL model (5). Addictive sensations, or inflammatory and oxidative responses triggered by smoking, may contribute to dysregulation of the primary biomarkers of AL (71,72).…”
Section: Discussionmentioning
confidence: 97%
“…It has been previously known that smoking and/or obesity affect stress. 21,22 Seborrheic dermatitis, which was removed in the multivariate analysis, seems to be a confounding factor that shows correlations with smoking and stress. 23,24 Likewise, blue-collar workers tended to smoke more (P \ .001) and to be more obese (P = .022) than students, indicating that occupation is also a confounding factor for PHG.…”
Section: Discussionmentioning
confidence: 99%